Gender Discrimination in Property Rights - Marco Casari; Maurizio Lisciandra (Institute for the Study of Labor (IZA), 2014)
Starting from the medieval period, women in the Italian Alps experienced a progressive erosion in property rights over the commons. We collected documents about the evolution of inheritance regulations on collective land issued by hundreds of peasant communities over a period of six centuries (13th-19th). Based on this original dataset, we provide a long-term perspective of decentralized institutional change in which gender-biased inheritance systems emerged as a defensive measure to preserve the wealth of community insiders. This institutional change had implications also for the protection from economic shocks, for population growth, and for marriage strategies.
Keywords: J16; N53; Q20; 330; land rights; endogamy; migrations; common property